PENERAPAN PEMBELAJARAN KOOPERATIF TGT BOLA BASKET UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMA (Department of Physical Education, Sport, Health and Recreation, 2014)
The problem in this study is how the application of cooperative learning model TGT basketballgame?. This study aims to mengetahuhi application of the model and to improvestudent learning outcomes through the implementation of cooperative learning in the learningTGT Physical Education, Sport and Health. This study uses classroom action research. Inthe implementation of the first cycle and second cycle of meetings held 1 meeting. The subjectswere 4 class XI IPS 2 Pemalng SMA. Instruments used in data collection obtained fromobservations during the learning and test performance. Based on the results, that there is anincrease in the learning process observations in each cycle.This formula was tested with hakewith results , Meaning that if more than 0.7, it can be stated that the increase in height(hight gain) and increased mastery of student learning outcomes in each cycle, the first cycleof 53.95% and 94.7% for the second cycle of the 38 number. Based on the above results, it canbe concluded that the application of cooperative learning model TGT basketball games canimprove student learning outcomes in class XI IPS 4 SMA Negeri 2 Pemalang.